2023
DOI: 10.38212/2224-6614.3460
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol stimulates StAR expression and progesterone production by GPER-mediated downregulation of Snail expression in human granulosa cells

Abstract: Steroidogenic acute regulatory protein (StAR) plays a critical role in the regulation of progesterone (P4) production. Resveratrol (RSV), a natural polyphenol, has beneficial effects on reproductive function. However, its effects on StAR expression and P4 production in human granulosa cells remain undetermined. In this study, we showed that treatment of RSV upregulated StAR expression in human granulosa cells. G protein-coupled estrogen receptor (GPER) and ERK1/2 signaling were involved in RSV-stimulated StAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Another study discovered that suppressing lipid metabolism in bovine GCs decreased P4 secretion, which could potentially influence follicle growth [64]. Studies on rat and human GCs found that RES increased the levels of StAR genes and proteins and increased P4 secretion [29,30]. Another study found that 10 µM RES analog (2-hydroxy-3,5,40-trimethoxystilbene) significantly increased the secretion of P4 by porcine GCs [73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study discovered that suppressing lipid metabolism in bovine GCs decreased P4 secretion, which could potentially influence follicle growth [64]. Studies on rat and human GCs found that RES increased the levels of StAR genes and proteins and increased P4 secretion [29,30]. Another study found that 10 µM RES analog (2-hydroxy-3,5,40-trimethoxystilbene) significantly increased the secretion of P4 by porcine GCs [73].…”
Section: Discussionmentioning
confidence: 99%
“…RES protects human GCs from induced oxidative stress [28]. It has also been reported that RES can upregulate StAR expression and promote P4 production in rat and human GCs [29,30]. Domestic yaks (Bos grunniens) are essential for Tibetans residing in the high-altitude regions of the Qinghai-Tibetan Plateau and surrounding areas, supplying meat, milk, and various other essentials in a harsh environment where survival of most other domesticated animal species is challenging [31].…”
Section: Introductionmentioning
confidence: 99%